The Antistaphylococcal Activity of Citropin 1.1 and Temporin A against Planktonic Cells and Biofilms Formed by Isolates from Patients with Atopic Dermatitis: An Assessment of Their Potential to Induce Microbial Resistance Compared to Conventional Antimicrobials - Malgorzata Dawgul; Wioletta Baranska-Rybak; Lidia Piechowicz; Marta Bauer; Damian Neubauer; Roman Nowicki; Wojciech Kamysz (MDPI AG, 2016)
Staphylococcus aureus (SA) colonizes the vast majority of patients with atopic dermatitis (AD). Its resistance to antibiotics and ability to form biofilms are the main origins of therapeutic complications. Endogenous antimicrobial peptides (AMPs) exhibit strong activity against SA, including antibiotic resistant strains as well as bacteria existing in biofilm form. The purpose of the present work was to determine the antistaphylococcal activity of two amphibian peptides against SA isolated from patients with AD. The AMPs demonstrated permanent activity towards strains exposed to sublethal concentrations of the compounds and significantly stronger antibiofilm activity in comparison to that of conventional antimicrobials. The results suggest the potential application of amphibian AMPs as promising antistaphylococcal agents for the management of skin infections.